Sea star stellaster childreni (echinodermata: asteroidea) from exclusive economic zone Bintulu and Miri, Sarawak - Lee, Suet Yee (Universiti Malaysia Sarawak (UNIMAS), 2016)
Seastar locally known as "Tapak Sulaiman" which beloging to class asteroidea, phylum echinodermata. In Malaysia, study of sea stars had been carried out in coastal water near Merambong Shoal, Johor and coral reef in the Central South China Sea. However, there is no documentation on diversity of sea stars inhabiting Sarawak EEZ. Therefore, the aim of this research is to identify sea star collected from EEZ near Bintulu and Miri, Sarawak based on morphological data, anatomy data and cytochrome oxidase I (COI) gene analysis. In addition, diet analysis, distribution and abudance of stellaster childreni hab been carried out. About 3.23% (n=7) specimens were found in EEZ Miri and 96.77% (n=210) specimens were found in EEX Bintulu. However, the distribution and abudance of S. childreni in this study are still in underestimated because it is bycatch organism.